Producers' cooperation within or against cooperative agricultural institutions? The case of reindeer husbandry in Post-Soviet Russia - Vladimirova, Vladislava (Journal of Rural Studies, 2017)
With the advance of economic neoliberalization along with the green economy paradigm that aims to alleviate rapid climate change, discussions of the rationale of cooperative organization of food production have come to the fore. This paper contributes to the scholarly understanding of motivations for cooperative organization of production by taking up empirical illustrations from the European North of Russia, where despite expectations of privatization after the dissolution of the Soviet Union, the cooperative organization of reindeer husbandry often persists, as a heritage of the Soviet state enterprises ( sovkhozes ). The paper aims at advancing the analysis of cooperative reindeer husbandry and its rationales employing ideas within the field of substantivist economic anthropology of postsocialism that started with Karl Polanyi's vision of the embedded economy (Polanyi, 1944). Further, I have employed the ideas of the renowned study by Caroline Humphrey of Soviet state farms as total social institutions (Humphrey, 1998) as well as Stephen Gudeman's dialectical approach to the economy (Gudeman, 2001). The analysis shows that the cooperative organization of reindeer husbandry reproduces the economic and social patterns that were developed in the Soviet period, perhaps also adapting and incorporating elements of traditional indigenous social orders. Such social arrangements and the accompanying moral values are embedded in the reindeer herding economy, and it is their persistence that indigenous people achieve through adhering to cooperative values.
Keywords: Eurasian studies; agricultural societies; agriculture - Russia; cooperative organization; embedded economy; farmers & the environment; food production - environmental aspects; reindeer farming; substantivism

An anthropological reading of the policies of international development: export competitiveness as a conjunctural case study - Shakya, Mallika (Dialectical Anthropology, 2017)
Drawing on ethnography of the World Bank's private sector development program, this paper explores the ways in which discussions of export competitiveness emerged in the past decade or so and how they interacted with larger discourses on solidarity and development. The immediate context within which this idea emerged was that of the structural adjustment programs (SAPs) which had maintained that the public regulation of the private economy compromises on industrial productivity (and by extension distributive social justice). But it would be naïve to think that alternative ideologies have not tried to insert themselves within the Bank's neoliberal discourse on development. If anything, discursive narratives suggest that the very notion of export competitiveness initially worked to justify the role of the state in regulating and incubating the private sector in developing countries even if these attempts became disembedded from their local contexts in the long run. This paper contextualizes this specific encounter on export competitiveness within the broader discourse of development and economic anthropology to examine the discursive politics of policy and knowledge in the global aid industry.
Keywords: IFIs; World Bank; anthropology; competition (economics); competitiveness; development; disembeddedness; economic liberalization; embeddedness; ethnology; human economy; structural adjustment program (SAP)

The Anthropocene and anthropology - Hann, Chris (European Journal of Social Theory, 2017)
Noting a lack of consensus in the recent literature on the Anthropocene, this article considers how social anthropologists might contribute to its theorizing and dating. Empirically it draws on the author’s long-term fieldwork in Hungary. It is argued that ethnographic methods are essential for grasping subjectivities, including temporal orientations and perceptions of epochal transformation. When it comes to historical periodization, however, ethnography is obviously insufficient and proposals privileging the last half-century, or just the last quarter of a century, seem inadequate. Influential theories, which define ‘modernity’ in terms of developments emanating from the countries of the North Atlantic in the sixteenth to the nineteenth centuries (Gellner, Polanyi, Wolf), remain partial and Eurocentric. To comprehend the social preconditions of the Anthropocene in a holistic fashion (the crucial contribution of comparative anthropology), it is necessary to follow Jack Goody and trace how the urban revolutions of the Bronze Age united Eurasia through the diffusion of new forms of economy, polity and cosmology.
Keywords: Eurasia; GOODY, Jack, 1919-2015; Hungary; anthropocene; anthropocene epoch; anthropology; cosmology; ethnology; social anthropology; socialism